The Palestinian electoral system: a comparative analytical study - Elshobake, Mohammed R. M. (Intelligentia Resources, 2023)
Elections stand as the cornerstone of any democratic system, representing a distinctive mechanism for the selection of presidents and representatives in accordance with the electoral framework of a given state. This research employs an analytical descriptive approach coupled with a comparative analysis of the Egyptian and Jordanian legal landscapes. Delving into the multifaceted concept of elections, it explores its legal standing, election systems, and methodologies adopted in diverse legislative frameworks. The study asserts that elections embody a legal authority, sanctioned by law to empower the electorate for the collective benefit of society. It discerns a significant legal nuance, categorizing the legal status of elections in Palestinian and Jordanian legislations as an individual right, while in the Egyptian context, it assumes the character of both a right and a role. Furthermore, the research underscores the suitability of the proportional representation method for Palestine, emphasizing its alignment with democratic principles, universal legislation, and foundational laws. As a crucial recommendation, the study advocates for the imperative need to conduct presidential and parliamentary elections in Palestine, aligning with democratic ideals and established legal norms. Additionally, it calls for essential amendments to the Palestinian election law to formalize the proportional representation system in parliamentary elections, thereby fostering a more inclusive and representative democratic process.